Effect Size Discovery Learning Model on Students Critical Thinking Skills - Everhard Markiano Solissa; Haetami Haetami; Via Via Yustita; Tomi Apra Santosa; Syafruddin Syafruddin (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the effect size of the discovery model on students' critical thinking skills. This type of research is meta-analysis research. The research sample comes from the analysis of 10 national and international journals indexed by SINTA, Scopus and Web of Science. The data source search process comes from Google Scholar, ScienceDirect, Eric and Wiley. The keywords for searching data sources are discovery learning model and critical thinking skills. Data collection techniques were direct observation and documentation. Data analysis is statistical analysis by calculating the effect size of each study with the help of JSAP. The results showed that the average effect size was 0.90 with very high criteria, the average value of the experimental class was 85. 90 and the control class was 72.10 and the N-gain value was 0.52. These findings indicate a positive effect of the discovery learning model on students' critical thinking skills. The discovery model helps students be more active and have higher-level thinking skills in learning